Efficacy and safety of a SOD1-targeting artificial miRNA delivered by AAV9 in mice are impacted by miRNA scaffold selection - Shukkwan K. Chen; Zachary C.E. Hawley; Maria I. Zavodszky; Sam Hana; Daniel Ferretti; Branka Grubor; Michael Hawes; Shanqin Xu; Stefan Hamann; Galina Marsh; Patrick Cullen; Ravi Challa; et al. (Elsevier, 2023)
Toxic gain-of-function mutations in superoxide dismutase 1 (SOD1) contribute to approximately 2%-3% of all amyotrophic lateral sclerosis (ALS) cases. Artificial microRNAs (amiRs) delivered by adeno-associated virus (AAV) have been proposed as a potential treatment option to silence SOD1 expression and mitigate disease progression. Primary microRNA (pri-miRNA) scaffolds are used in amiRs to shuttle a hairpin RNA into the endogenous miRNA pathway, but it is unclear whether different primary miRNA (pri-miRNA) scaffolds impact the potency and safety profile of the expressed amiR in vivo. In our process to develop an AAV amiR targeting SOD1, we performed a preclinical characterization of two pri-miRNA scaffolds, miR155 and miR30a, sharing the same guide strand sequence. We report that, while the miR155-based vector, compared with the miR30a-based vector, leads to a higher level of the amiR and more robust suppression of SOD1 in vitro and in vivo, it also presents significantly greater risks for CNS-related toxicities in vivo. Despite miR30a-based vector showing relatively lower potency, it can significantly delay the development of ALS-like phenotypes in SOD1-G93A mice and increase survival in a dose-dependent manner. These data highlight the importance of scaffold selection in the pursuit of highly efficacious and safe amiRs for RNA interference gene therapy.